2002
DOI: 10.1002/1521-3773(20021202)41:23<4467::aid-anie4467>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Attachment of Molecules at a Molecular Printboard by Multiple Host–Guest Interactions

Abstract: Dedicated to Professor Manfred T. Reetz on the occasion of his 60th birthdayThe exact positioning of molecules on surfaces has become essential for the development of molecular electronics [1] and biochip applications, [2] as well as for conducting single molecule experiments. Commonly, one of two possible routes is followed, either by chemically reacting molecules to surfaces or to anchoring molecules present at a surface, or by physisorption, that is, the use of nonspecific physical interactions between mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
144
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(148 citation statements)
references
References 4 publications
4
144
0
Order By: Relevance
“…Ac urrent topic in polymer science is surface functionalization, and supramolecular chemistry opens up new opportunities for surface chemistry.T he expression "molecular printboards" coined by Reinhoudt and Huskens refers to monolayers of CDs on surfaces, [144] and several materials have been used in this regard, for example,g old, [144] Si, [41] and SiO 2 .…”
Section: Surface Modificationsmentioning
confidence: 99%
“…Ac urrent topic in polymer science is surface functionalization, and supramolecular chemistry opens up new opportunities for surface chemistry.T he expression "molecular printboards" coined by Reinhoudt and Huskens refers to monolayers of CDs on surfaces, [144] and several materials have been used in this regard, for example,g old, [144] Si, [41] and SiO 2 .…”
Section: Surface Modificationsmentioning
confidence: 99%
“…They have also been extensively used as chiral selectors in separation technology [18] and it has been shown that cyclodextrin based polymers could be used as sensitive layers in chiral sensing by SPR [16]. Reinhoudt has extensively studied the ability of these macrocycle to form well packed SAMs on gold surfaces [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…[15,16] Furthermore, the multivalent supramolecular interactions between these host-guest molecules to construct selfassembled mono-or multi-layers on different materials (e.g., gold or silica) were also investigated in the past. [17,18] Nanocapsules are considered one of the most important polymeric self-assembled systems as they can find diverse applications ranging from drug delivery to cosmetics or sensing. [19][20][21] Jiang and co-workers have prepared stable submicrometer size micelles by adding a large volume of water to a mixed solution of ADA-derivatized poly-(tertbutyl acrylate as hydrophobic polymer with bCD-modified poly-(glycidylmethacrylate) in DMF.…”
Section: Introductionmentioning
confidence: 93%